Integrasi REST API Rule-Based Dan WebGIS Untuk Otomasi Diseminasi Gempabumi - Iqbal Jabar Marjan; Dean J. Samuel Kembuan; Fatih Jalalhaq Ratumboba; Ottopianus Mellolo; Venny Vita Ponggawa (Fakultas Teknik Universitas Hamzanwadi, 2026)
The speed of disaster information delivery is often hindered by lengthy technical data bureaucracy. At the BMKG Manado Geophysical Station, the dissemination process post-data acquisition from the SeisComP3 machine still heavily relies on the manual intervention of the Duty Officer. This condition triggers work queues, especially when officers must sort through hundreds of micro-earthquake anomalies before copying reports to digital communication groups. To solve this problem, this research uses the Research and Development (R&D) method to design a Zero-Touch Automation ecosystem. We integrated a REST API backend equipped with a Rule-Based System algorithm to independently select seismic parameters, then seamlessly connected it with a WebGIS frontend and Telegram Bot. Quantitative test results in the field indicate that this architecture successfully performs smart data routing; earthquakes meeting the alert threshold are immediately forwarded as early warnings autonomously with an average latency of less than 3 seconds. As a scientific and practical contribution, the implementation of this system, which is equipped with a dynamic analytic panel, is proven to cut crucial reporting times from minutes to seconds, and effectively minimize human error risks in the observation room.